2011
DOI: 10.1002/pssb.201046107
|View full text |Cite
|
Sign up to set email alerts
|

Optical limiting response of Ag2S nanoparticles synthesized by laser ablation of silver target in DMSO

Abstract: Silver sulfide nanoparticles (Ag 2 S NPs) were synthesized by nanosecond pulsed laser ablation of a silver plate in dimethyl sulfoxide. Ultraviolet-visible absorption spectrometry, X-ray diffraction, and transmission electron microscopy were used to characterize the obtained nanocrystal samples. The mechanisms for optical limiting performance of an Ag 2 S NP colloid were investigated under exposure to nanosecond pulsed laser irradiation at 532 nm. The observed aperture dependence of the Ag 2 S NP limiting perf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
12
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(14 citation statements)
references
References 36 publications
2
12
0
Order By: Relevance
“…Elemental analysis using energy-dispersive X-ray analysis (EDAX) shows Ag/S ratio remains unchanged (1.9:1) before and after the annealing. Therefore, the only possible explanation for this partial appearance of excitonic feature after this mild annealing can be because of improvement of crystallinity through removal of defects. , Further increase in annealing temperature to 200 °C leads to the segregation of Ag impurity phase, similar to a previous report . Results of cation exchange reaction infer that unwanted defect-related broad absorption blurs the features of excitonic absorption and quenches the excitonic emission.…”
supporting
confidence: 77%
See 2 more Smart Citations
“…Elemental analysis using energy-dispersive X-ray analysis (EDAX) shows Ag/S ratio remains unchanged (1.9:1) before and after the annealing. Therefore, the only possible explanation for this partial appearance of excitonic feature after this mild annealing can be because of improvement of crystallinity through removal of defects. , Further increase in annealing temperature to 200 °C leads to the segregation of Ag impurity phase, similar to a previous report . Results of cation exchange reaction infer that unwanted defect-related broad absorption blurs the features of excitonic absorption and quenches the excitonic emission.…”
supporting
confidence: 77%
“…Please note that Figure d also suggested ∼140 °C is the optimum temperature to anneal out defects from cation-exchanged Ag 2 S NCs. Higher temperatures may lead to the starting of partial segregation of Ag phase …”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Nanoparticles constituted of metallic salts are also attractive for NLO and OL applications. For instance, Ag 2 S NPs were synthesized by ns pulsed laser ablation of a silver plate in dimethyl sulfoxide, 545 and their OL performance was investigated under irradiation with ns pulses at 532 nm. Ag 2 S NPs samples displayed OL behavior, and the observation of an asymmetrical configuration of the data indicated that nonlinear scattering was occurring in this materials.…”
Section: Metal Nanoparticlesmentioning
confidence: 99%
“…[1][2][3][4][5] Bulk monoclinic a-Ag 2 S, with a band gap of 1.1 eV, a relatively large absorption coefficient, and excellent optical limiting properties, has been synthesized and used in photoconductors, photovoltaic cells, photo detectors, solar cells, etc. [6][7][8][9][10][11][12][13][14][15][16][17][18][19][20][21][22][23][24] Recently, the NIR photoluminescent (PL) property of Ag 2 S nanocrystals has been developed. [25][26][27] Wang and co-workers reported the preparation of single-crystalline monodisperse Ag 2 S nanocrystals with a size of about 10 nm by using a single source precursor, which yield the first observation to present the NIR emission at 1058 nm.…”
Section: Introductionmentioning
confidence: 99%